2005
DOI: 10.1111/j.1551-2916.2005.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Synthesis of Nanosized Bismuth Ferrite by Soft Chemical Route

Abstract: The present research describes a simple low‐temperature synthesis route of preparing bismuth ferrite nanopowders through soft chemical route using nitrates of Bismuth and Iron. Tartaric acid is used as a template material and nitric acid as an oxidizing agent. The synthesized powders are characterized by X‐ray diffractometry, thermogravimetry and differential thermal analysis, infrared spectroscopy, and scanning electron microscopy. The particle size of the powder lies between 3 and 16 nm. In the process, phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
154
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(160 citation statements)
references
References 10 publications
3
154
1
2
Order By: Relevance
“…Even the utilization of EDTA, known as a very strong complexing agent with four carboxylic acid groups, was unsuccessful (Liu et al 2010). It is interesting to note that the classical Pechini synthesis route (Pechini 1967) with citric acid and ethylene glycol has been reported both to give phase-pure (Popa et al 2007) materials and to give secondary phases (Ghosh et al 2005a). However, in the successful experiment, EG was used as a solvent, i.e.…”
Section: Bismuth Ferritementioning
confidence: 99%
“…Even the utilization of EDTA, known as a very strong complexing agent with four carboxylic acid groups, was unsuccessful (Liu et al 2010). It is interesting to note that the classical Pechini synthesis route (Pechini 1967) with citric acid and ethylene glycol has been reported both to give phase-pure (Popa et al 2007) materials and to give secondary phases (Ghosh et al 2005a). However, in the successful experiment, EG was used as a solvent, i.e.…”
Section: Bismuth Ferritementioning
confidence: 99%
“…To date, synthesis of pure phase BiFeO 3 is still a challenging task. So far, bismuth ferrite particles were prepared mostly by the solid state and solution chemistry methods (i.e., precipitation/co-precipitation, solgel, hydrothermal and sonochemical) [13][14][15][16][17][18][19]. However, it resulted in the formation of coarser particles.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases these methods seem successful in order to obtain BiFeO 3 nanoparticles [74][75][76][77][78], but divergences are also frequent. Actually it has been suggested that the BiFeO 3 obtained by these wet chemistry routes evidences a metastable behavior and under certain conditions -again contradictory [44,68]-it decomposes leading to secondary phase byproducts.…”
Section: Mixed Oxides Synthesismentioning
confidence: 99%